ER stress mediated inflammation in cancer pathogenesis - S. Jalajakumari, Soumya; Ramesh, Renu; S. Nair, Achuthsankar (Trends in Immunotherapy, 2024)
Inflammation is a complex process which is associated with the initiation and progression of cancer. Prolonged Endoplasmic Reticulum (ER) stress triggers inflammation which is a key factor associated with cancer pathogenesis. ER stress also contributes to immune suppression in inflammatory and tumor microenvironment. It stimulates the production of pro-inflammatory cytokines by regulating the activation of various transcription factors and inflammatory signalling pathways. Targeting ER stress is an exciting possibility that can be used as a therapeutic strategy for cancer treatment. This mini review focuses on the emerging link between ER stress-induced inflammatory responses in cancer development.